Impact Of Institutional Variables On Foreign Direct Investment "The Middle East And North Africa" - اسماعيل رولا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The paper explores the linkages between institutions and foreign direct investment inflows. Using econometric techniques for a data sample of 4 developing countries in the Middle East and North Africa and the period 2006 to 2019, we identify those indicators that matter most for the activities of multinational corporations. Overall, 7 different indicators for institutions are employed in the empirical analysis (Control of Corruption , Government Effectiveness, Political Stability and Absence of Violence/Terrorism, Regulatory Quality, Rule of Law, Voice and Accountability, Corruption and Doing business). The results show that Regulatory Quality, Government Effectiveness and Political Stability and Absence of Violence/Terrorism are significant determinants of foreign investment inflows.